The chemistry and pharmacology of alkaloids and allied nitrogen compounds from Artemisia species: A review. (27th August 2019) - Ur Rashid, Mamoon; Alamzeb, Muhammad; Ali, Saqib; Ullah, Zahoor; Shah, Zafar Ali; Naz, Ishrat; Khan, Muhammad Rafiullah
Abstract : Several reviews have been published on Artemisia 's derived natural products, but it is the first attempt to review the chemistry and pharmacology of more than 80 alkaloids and allied nitrogen compounds obtained from various Artemisia species (covering the literature up to June 2018). The pharmacological potential and unique skeleton types of certain Artemisia 's alkaloids provoke the importance of analyzing Artemisia species for bioactive alkaloids and allied nitrogen compounds. Among the various types of bioactive Artemisia 's alkaloids, the main classes were the derivatives of rupestine (pyridine–sesquiterpene), lycoctonine (diterpene), pyrrolizidine, purines, polyamine, peptides, indole, piperidine, pyrrolidine, alkamides, and flavoalkaloids. The rupestine derivatives are Artemisia 's characteristic alkaloids, whereas the rest are common alkaloids found in the family Asteraceae and chemotaxonomically links the genus Artemisia with the tribes Anthemideae. The most important biological activities of Artemisia 's alkaloids are including hepatoprotective, local anesthetic, β ‐galactosidase, and antiparasitic activities; treatment of angina pectoris, opening blocked arteries, as a sleep‐inducing agents and inhibition of HIV viral protease, CYP450, melanin biosynthesis, human carbonic anhydrase, [3H]‐AEA metabolism, kinases, and DNA polymerase β 1 . Some of the important nitrogen metabolites of Artemisia include pellitorine, zeatin, tryptophan, rupestine, and aconitine analogs, which need to be optimized and commercialized further. Abstract : A review on the chemistry and pharmacology of alkaloids and allied nitrogen compounds from Artemisia is presented for the first time, covers the literature up to June 2018. The structures of more than 80 alkaloids including the derivatives of rupestine, lycoctonine, pyrrolizidine, purine, indole, polyamine, peptides, alkamides, piperidine, pyrrolidine, ceramide/cerebroside, aromatic/non‐aromatic amines, benzodiazepines, flavoalkaloids, quinazoline, piperazine, pyrazine, pyridine, pyrrole, and 1, 4‐diaza‐2, 5‐dioxobicyclo[4.3.0]nonane are explained. Inhibition of HIV viral protease, melanin biosynthesis, and anti‐parasitic bio‐activities is associated with Artemisia's nitrogen metabolites.